2020
DOI: 10.1186/s12885-020-07333-y
|View full text |Cite
|
Sign up to set email alerts
|

Short-course radiation followed by mFOLFOX-6 plus avelumab for locally-advanced rectal adenocarcinoma

Abstract: Background Current standard practice for locally advanced rectal cancer (LARC) entails a multidisciplinary approach that includes preoperative chemoradiotherapy, followed by total mesorectal excision, and then adjuvant chemotherapy. The latter has been accompanied by low compliance rates and no survival benefit in phase III randomized trials, so the strategy of administering neoadjuvant, rather than adjuvant, chemotherapy has been adapted by many trials, with improvement in pathologic complete res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…In addition, immune checkpoint inhibitors such as durvalumab, avelumab, and nivolumab and other novel agents such as peposertib, a DNA protein kinase inhibitor, and aflibercept, an angiogenesis inhibitor, are being investigated in a TNT setting. 32 , 33 , 34 , 35 , 36 A list of recent and ongoing TNT trials that are yet to be published is included in eTable 2 in the Supplement . 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, immune checkpoint inhibitors such as durvalumab, avelumab, and nivolumab and other novel agents such as peposertib, a DNA protein kinase inhibitor, and aflibercept, an angiogenesis inhibitor, are being investigated in a TNT setting. 32 , 33 , 34 , 35 , 36 A list of recent and ongoing TNT trials that are yet to be published is included in eTable 2 in the Supplement . 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…Shamseddine et al conducted a phase 2 trial for locally advanced rectal cancer (T2N+ or T3 or T4a) of short-course radiation (25 Gy in five fractions) followed by six cycles of FOLFOX plus avelumab and total mesorectal excision and found a CR rate of 25%. 22 Rahma et al reported on 185 rectal cancer patients, CR after neoadjuvant CRT +/À pembrolizumab did not show any difference, although long-term survival data are awaited. Grade 3-4 adverse events were slightly increased in the pembrolizumab arm (48.2%) vs the control arm (37.3%) during CRT.…”
Section: Colorectal Cancermentioning
confidence: 98%
“…Shamseddine et al . conducted a phase 2 trial for locally advanced rectal cancer (T2N+ or T3 or T4a) of short‐course radiation (25 Gy in five fractions) followed by six cycles of FOLFOX plus avelumab and total mesorectal excision and found a CR rate of 25% 22 . Rahma et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, there were still 34.6% of patients who had disease progression after treatment. Immunotherapy, targeted therapies and triplet chemotherapy which might facilitate the removal of potential micrometastasis and the strategy of total neoadjuvant therapy could be considered, to improve the treatment efficacy [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%